AUDIT PROFESSION IN THE SHADOW OF THE COVID -19 - A PERCEPTION OF AUDITORS IN REPUBLIC OF NORTH MACEDONIA - Bozhinovska lazarevska, Zorica; Trpeska, Marina; Atanasovski, Atanasko; Dionisijev, Ivan (Faculty of Economics - Skopje, Ss Cyril and Methodius University, 2020)
The virtual practice has posed serious challenges and opened many dilemmas for the auditors. How to obtain sufficient and appropriate audit evidence in the absence of communication with the client, to assess the risks of material misstatement, to recognize the symptoms of fraud, to check subsequent events, to assess the ability for ‘going concern’, to exercise the required level of professional skepticism, and how to write an audit report in which the auditor will offer a reasonable assurance to users of the opinion expressed. Health experts warn that even in the post-COVID-19 period, the social distance will be an integral part of our lives. In that regard, IFAC also points out the need to prepare auditors for work in the so-called "the new normal". The paper researches how the COVID-19 pandemic affects the audit profession in the Republic of North Macedonia. For that purpose, our research is based on a survey distributed to the certified auditors, members of IORRM (Institute of Certified Auditors of the Republic of North Macedonia). From the questions asked, we have concluded whether and how much the pandemic has changed the approach of auditors in conducting audit engagements, how auditors have managed to amortize the initial shock, whether they have prepared a strategy for virtual practice in the environment of the so-called "new normal" and what are the biggest challenges they expect to face in the post-COVID world. In addition to analyzing data obtained from the survey, documents related to the impact of COVID-19 pandemic worldwide are used, as well as other literature and scientific papers on how the audit profession responds to the COVID crisis.
Keywords: Pandemic; COVID-19; Audit Profession; Auditors